2004
DOI: 10.1038/sj.cr.7290227
|View full text |Cite
|
Sign up to set email alerts
|

Uterine receptivity and the plasma membrane transformation

Abstract: This review begins with a brief commentary on the diversity of placentation mechanisms, and then goes on to examine the extensive alterations which occur in the plasma membrane of uterine epithelial cells during early pregnancy across species. Ultrastructural, biochemical and more general morphological data reveal that strikingly common phenomena occur in this plasma membrane during early pregnancy despite the diversity of placental types-from epitheliochorial to hemochorial, which ultimately form in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
204
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(210 citation statements)
references
References 98 publications
(114 reference statements)
4
204
0
2
Order By: Relevance
“…3,[42][43][44] In the present study, using multiple genetic and cellular approaches combined with uterine conditional Rac1 depletion mouse model, we demonstrated that uterine Rac1 via Pak1-ERM signaling cascade ensures normal luminal epithelial integrity conducive to on-time embryo implantation. We also provided evidence that TNFα-Rac1-P38 signaling cascade is essential for uterine luminal epithelium elimination during postimplantation uterine development ( Figure 9).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…3,[42][43][44] In the present study, using multiple genetic and cellular approaches combined with uterine conditional Rac1 depletion mouse model, we demonstrated that uterine Rac1 via Pak1-ERM signaling cascade ensures normal luminal epithelial integrity conducive to on-time embryo implantation. We also provided evidence that TNFα-Rac1-P38 signaling cascade is essential for uterine luminal epithelium elimination during postimplantation uterine development ( Figure 9).…”
Section: Discussionmentioning
confidence: 91%
“…44 The columnar luminal epithelium transits to cuboidal shape and microvilli on the apical plasma show a retraction which makes the apical plasma more flat. [44][45][46][47] Moreover, tight junction molecules, such as Occludin, ZO-1 and Claudins are dynamically expressed in the periimplantation uterus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implantation involves the apposition, attachment, and, in many species, the invasion of the blastocyst into the uterus (1). In particular, structural and molecular changes occur in the luminal epithelia that allow the embryo to attach and invade the uterus (2). Epithelial changes are followed by remodeling of the endometrial stroma, generally known as "decidualization," i.e., the transformation of endometrial stromal fibroblasts into decidual stromal cells, as well as modifications of the endometrial vascular bed (3).…”
mentioning
confidence: 99%
“…3(E)) In contrast, the expression of ERα target genes (ltf, muc1) was significantly higher in Lgr4 K5 KO . [14][15][16] However, the phosphorylation level of Ser-118 and Ser-104/106 of ERα was not elevated in Lgr4 K5 KO luminal cells, indicating that other phosphorylation sites of ERα might have been affected by the LGR4 deletion (Supplemental Fig. 1).…”
Section: Primermentioning
confidence: 99%